FRI0521 Secukinumab provides sustained improvements in work productivity and health related quality of life in patients with active psoriatic arthritis: 2-year results from future 1 and future 2. (15th June 2017) - Strand, V; FitzGerald, O; Coates, LC; Walsh, JA; Cañete, JD; Bhosekar, V; Pricop, L; Gandhi, K; Jugl, S
Abstract : Background: Patients (pts) with PsA experience significant impairment of work productivity (WP) and health-related QoL (HRQoL). Secukinumab (SEC) has previously been shown to rapidly improve symptoms, physical function and HRQoL in pts with active PsA. 1, 2 Objectives: To assess the impact of SEC on WP and HRQoL through 2 years (yrs) in TNF inhibitor (TNF)-naïve PsA pts and those with an inadequate response or intolerance to TNF inhibitors (TNF-IR). Methods: 606 and 397 pts were randomized to SEC or placebo (PBO) in FUTURE 1 (10 mg/kg IV followed by 150 or 75 mg SC) and FUTURE 2 (300, 150 or 75 mg SC), respectively. PBO pts were re-randomized to SEC at Wk 16/24. WP was assessed using the WP and Activity Impairment–General Health (WPAI-GH) questionnaire. WPAI-GH includes 6 questions to measure absenteeism, presenteeism, work productivity and impairments in unpaid activity because of health problems during the preceding 7 days. HRQoL was assessed using the PsAQoL questionnaire, encompassing 20 statements that pts rate as true or false on the day of completion. Across both trials, approximately 68% of pts were TNF-naïve and 32% were TNF-IR. Observed data are presented from the full analysis set and in subgroups stratified by prior TNF exposure. Only data with approved doses of SEC (300 and 150 mg) are shown. Results: In FUTURE 1, 88 of 202 in the SEC 150 mg group were employed and working at baseline (BL); 61 of 100 and 59 of 100 were employed and working at BL in the SEC 300 mg and 150 mg groups of FUTURE 2, respectively. Improvements in all elements of WPAI were reported with SEC 300 and 150 mg in the overall population at Wk 16; responses were sustained through Wk 104 (Table). The greatest improvements were seen in presenteeism (–10.0), work productivity (–10.3) and activity impairment (–14.1), which corresponded to improvements from BL of approximately 29%, 26% and 30%, respectively in the overall population of FUTURE 1 at Wk 104; similar improvements were seen in FUTURE 2 at Wk 104 (300 mg: –14.4 [42%], –11.2 [33%] and –17.7 [38%]; 150 mg: –16.8 [50%], –16.8 [45%] and –18.5 [38%]). Sustained improvements in all elements of WPAI were also evident with SEC in TNF-naïve and TNF-IR pts in both FUTURE 1 and FUTURE 2. Improvements in PsAQoL were reported as early as Wk 4 and sustained through Wk 104. At Wk 104 of FUTURE 2, PsAQoL scores had improved by approximately 46% from BL with SEC 300 mg and 49% with SEC 150 mg in the overall population. Similar improvements were seen in TNF-naïve (47% and 51%, respectively) and TNF-IR pts (45% and 45%, respectively). Consistent results were reported in FUTURE 1. The efficacy of SEC was consistent regardless of concomitant MTX use. Conclusions: SEC provided sustained improvements in WP and PsAQoL in pts with PsA for up to 104 wks, regardless of prior TNF exposure. References: McInnes. Lancet 2015;386:1137–46. Mease. NEJM 2015;373:1329–39. Disclosure of Interest: V. Strand Consultant for: AbbVie, Amgen, BMS, Celgene, Celltrion, CORRONA, Genentech/Roche, GSK, Janssen, Lilly, Merck, Novartis, Pfizer, Regeneron, Samsung, Sanofi, and UCB, O. FitzGerald Grant/research support from: Abbvie, BMS, Celgene, Janssen, MSD, Novartis, Pfizer, Sun Pharma, UCB, L. Coates Grant/research support from: Abbvie, BMS, Celgene, Janssen, Lilly, MSD, Novartis, Pfizer, Sun Pharma, UCB, J. Walsh Consultant for: Novartis, J. Cañete Consultant for: AbbVie, Boehringer Ingelheim, Celgene, Janssen, Lilly, Novartis, V. Bhosekar Employee of: Novartis, L. Pricop Employee of: Novartis, K. Gandhi Shareholder of: Novartis, Employee of: Novartis, S. Jugl Shareholder of: Novartis, Employee of: Novartis